ANALISA KOEFISIEN PRESTASI (COP) MESIN PENDINGIN PADA POWER HOUSE - Witanto, Yovan; Zuliantoni; Aritonang, Jefri Fanto (UNIB Press, 2024)
Refrigeration machines that cool water are called chillers. Chillers are air conditioners with an indirect cooling system. In this indirect cooling system, the refrigeration machine does not directly cool the air in each room. The refrigeration machine cools the demin water first, then the cold demin water is used to cool the air in the room. Cold demin water as a cooling medium to reduce the temperature of a large space in the Power house. In this study, an Analysis of the Coefficient of Performance (COP) of the Cooler in the Power house was conducted. The data taken for this study were the temperature of the refrigerant when it was released from the expansion valve (T4 = 0 ° C), the temperature when it was released from the evaporator (T1 = 9 ° C) and the temperature when it was released from the compressor (T2 = 77 ° C). At T4 the enthalpy value (h4) was obtained as 204.81 kj/kg, at T1 the enthalpy value h1 was 253.025 kj/kg, at T2 the enthalpy value (h2) was 263.582 kj/kg. Thus, the coefficient of performance (COP) obtained was 4.567.